The causal relationship between immune cells and Sjögren’s syndrome: a univariate, multivariate, bidirectional Mendelian randomized study - Zeng, Wen; Huang, Mu; Zeng, Yuanyuan; Pan, Jie; Qin, Fang; Liao, Xiaoling; Zheng, Leting; Lei, Ling (Frontiers in Medicine, 2024)
Immune cells are involved in the onset and progression of Sjögren's syndrome (SS). This study explored the causal relationship between immune signature cells and SS, which has not been fully elucidated. We conducted univariate, multivariate, and bidirectional Mendelian randomization to investigate the causal relationship between 731 immunological feature characteristic cells and SS pairs and explore the interaction of immune cells in SS. After false discovery rate correction, six immune cells were significantly associated with SS risk. Among them, CD24 on memory B cell, CD27 on IgD+CD24+B cell, CD28 on CD39+ secreting CD4 Treg cell , and CD80 on CD62L+mDC contributed to SS; CD3 on CD39+CD8+T cell and CD38 on IgD+CD38+B cell appeared to reduce SS risk. Pleiotropy and heterogeneity were not observed. Three immune cells exerted independent effects for SS; CD27 on IgD+CD24+B cell, CD80 on CD62L+mDC were risk factors; CD38 on IgD+CD38+B cell and one was a protective factor. Twentythree immune cells showed a reverse causal relationship with SS. This study reveals six immune cell types that may be critical in the pathogenesis of Sjogren's syndrome, which can help guide future clinical and basic research and to design therapeutic strategies from an immunological perspective.